Human cytomegalovirus neutralizing antibody-resistant phenotype is associated with reduced expression of glycoprotein H. - Li, L (1995)
We have characterized a neutralizing antibody-resistant mutant human cytomegalovirus (HCMV) obtained from a patient treated with a human monoclonal antiglycoprotein H (gH; unique long region 75) antibody. This virus exhibited resistance to several different neutralizing anti-gH murine monoclonal antibodies (MAbs), as well as to a polyvalent anti-gH serum. The resistant phenotype was unstable and could be maintained only by passage of plaque-purified virus under neutralizing MAb selection. In the absence of a MAb, the resistant phenotype reverted to a neutralizing antibody-sensitive phenotype within one passage. The predicted amino acid sequences of gH from the MAb-resistant and -susceptible parent viruses were identical. Biochemical analysis of the MAb-resistant and -susceptible parent viruses revealed a marked decrease of gH expression in the envelope of the MAb-resistant virus. Furthermore, propagation of the virus in various MAb concentrations resulted in the production of extracellular virions with various levels of resistance to the neutralizing activity of the MAb. These results suggest a mechanism for the generation of neutralizing antibody-resistant viruses which could evade host-derived antiviral antibody responses. In addition, our findings indicate that the stoichiometry of gH in the envelope of infectious HCMV virions is not rigidly fixed and therefore offer a simple explanation for production of phenotypic variants of HCMV through an assembly process in which the content of gH in the envelope of progeny virions varies randomly.